Analysis Determination of Growth Centers and Leading Commodities Based On Agricultural Sector Plantation Sub-sector In Sijunjung District - Urwathul Wusqa; Melinda Noer; Nuraini Budi Astuti (Baselang, 2022)
The study aims to identify (1) the district which has the growth potential in Sijunjung district-based facilities. The facilities used are agricultural facilities. the methode analysis used for this research is scallogram and index centrality. (2) to identify basic comodities in plantation subsector in each sub-district, the methode analysis is analysis location quentiont (LQ) and shift share analysis (SSA). the analytical method use is descriptive quantitative. The result of analysis show points out that the main growth center first hierarchy in Sijunjung is Kamang Baru with centrality index value of 719,9 and the main commodities of first priority is palm oil and Koto VII district with centrality index value of 682,5 The lead of plantation commodities in Koto VII are rubber in first priority and coconut in third priority.